Accuracy and Acceptability of Commercial-Grade Physical Activity Monitors in Older Adults - Hergenroeder, Andrea L. (J Aging Phys Act, 2018)
The aim of this study was to evaluate accuracy of seven commercial activity monitors in measuring steps in older adults with varying walking abilities and to assess monitor acceptability and usability. Forty-three participants (age = 87 ± 5.7 years) completed a gait speed assessment, two walking trials while wearing the activity monitors, and questionnaires about usability features and activity monitor preferences. The Accusplit AX2710 Accelerometer Pedometer had the highest accuracy (93.68% ±13.95%), whereas the Fitbit Charge had the lowest (39.12% ± 40.3%). Device accuracy varied based on assistive device use, and none of the monitors were accurate at gait speeds <0.08 m/s. Barriers to monitor usability included inability to apply monitor and access the step display. Monitor accuracy was rated as the most important feature, and ability to interface with a smart device was the least important feature. This study identified the limitations of the current commercial activity monitors in both step counting accuracy and usability features for older adults.